Neuromonitoring during general anesthesia in non-neurologic surgery. Issue 2 (July 2021) - Bonatti, Giulia; Iannuzzi, Francesca; Amodio, Sara; Mandelli, Maura; Nogas, Stefano; Sottano, Marco; Brunetti, Iole; Battaglini, Denise; Pelosi, Paolo; Robba, Chiara
Abstract : Cerebral complications are common in perioperative settings even in non-neurosurgical procedures. These include postoperative cognitive dysfunction or delirium as well as cerebrovascular accidents. During surgery, it is essential to ensure an adequate degree of sedation and analgesia, and at the same time, to provide hemodynamic and respiratory stability in order to minimize neurological complications. In this context, the role of neuromonitoring in the operating room is gaining interest, even in the non-neurolosurgical population. The use of multimodal neuromonitoring can potentially reduce the occurrence of adverse effects during and after surgery, and optimize the administration of anesthetic drugs. In addition to the traditional focus on monitoring hemodynamic and respiratory systems during general anesthesia, the ability to constantly monitor the activity and maintenance of brain homeostasis, creating evidence-based protocols, should also become part of the standard of care: in this challenge, neuromonitoring comes to our aid. In this review, we aim to describe the role of the main types of noninvasive neuromonitoring such as those based on electroencephalography (EEG) waves (EEG, Entropy module, Bispectral Index, Narcotrend Monitor), near-infrared spectroscopy (NIRS) based on noninvasive measurement of cerebral regional oxygenation, and Transcranial Doppler used in the perioperative settings in non-neurosurgical intervention. We also describe the advantages, disadvantage, and limitation of each monitoring technique.